Decorin knockdown affects the gene expression profile of adhesion, growth and extracellular matrix metabolism in C-28/I2 chondrocytes. - Mengying Wang; Zhengzheng Li; Meng Zhang; Hui Wang; Ying Zhang; Yiping Feng; Yinan Liu; Jinghong Chen (PLoS ONE, 2020)
Decorin is a member of small leucine-rich proteoglycan family, which is involved in multiple biological functions mainly as a structural and signaling molecule, and disturbances in its own metabolism plays a crucial role in the pathogenesis of osteoarthropathy. In this study, we aim to further explore the biological function of decorin and their role in human chondrocyte cell line, C28/I2. Lentivirus-mediated shRNA was applied to down-regulate decorin expression in C28/I2 chondrocytes. Effect of decorin knockdown on gene expression profiles was determined by RNA sequencing followed by bioinformatics analysis. MTT, adhesion assays and flow cytometry were used to investigate the effect of decorin knockdown on cell proliferation, adhesion, and apoptosis. sGAG content in the culture medium was determined by DMMB assay. Stably transfected C28/I2 cells were seeded onto the cancellous bone matrix gelatin (BMG) to construct tissue-engineered cartilage. The histological patterns were evaluated by H&E and Toluidine blue staining. In this study, 1780 differentially expressed genes (DEGs) including 864 up-regulated and 916 down-regulated genes were identified using RNA-Seq. The reliability of the gene expression was further verified by qRT-PCR. GO and KEGG pathway enrichment analysis revealed diverse cellular processes were affected by decorin silencing such as: cell adhesion, growth, and metabolism of extracellular matrix. In addition, we confirmed that down-regulation of decorin significantly suppressed cell proliferation and adhesion and induced apoptosis. The sGAG content in the media was significantly increased after decorin silencing. Engineered articular tissues in the decorin knockdown group exhibited cartilage destruction and proteoglycan loss as evidenced by H&E and Toluidine blue stains. Overall, this combined data helps to provide a comprehensive understanding of the roles of decorin following its knockdown in C28/I2 cells.